Optimization of pulsed electric field pre‐treatments to enhance health‐promoting glucosinolates in broccoli flowers and stalk. (15th October 2014) - Aguiló‐Aguayo, Ingrid; Suarez, Manuel; Plaza, Lucia; Hossain, Mohammad B; Brunton, Nigel; Lyng, James G; Rai, Dilip K
Abstract BACKGROUND The effect of pulsed electric field (PEF) treatment variables (electric field strength and treatment time) on the glucosinolate content of broccoli flowers and stalks was evaluated. Samples were subjected to electric field strengths from 1 to 4 kV cm−1 and treatment times from 50 to 1000 µs at 5 Hz. RESULTS Data fitted significantly (P < 0.0014) the proposed second‐order response functions. The results showed that PEF combined treatment conditions of 4 kV cm−1 for 525 and 1000 µs were optimal to maximize glucosinolate levels in broccoli flowers (ranging from 187.1 to 212.5%) and stalks (ranging from 110.6 to 203.0%) respectively. The predicted values from the developed quadratic polynomial equation were in close agreement with the actual experimental values, with low average mean deviations (E%) ranging from 0.59 to 8.80%. CONCLUSION The use of PEF processing at moderate conditions could be a suitable method to stimulate production of broccoli with high health‐promoting glucosinolate content. © 2014 Society of Chemical Industry